Medicinal uses and pharmacological properties of Terminalia kaiserana F.Hoffm. (Combretaceae family). - Maroyi, Alfred (Student’s Journal of Health Research Africa, 2025)
Background Terminalia kaiserana F.Hoffm. is a deciduous shrub or small tree widely used in traditional medicine in tropical Africa. This study was aimed at reviewing the medicinal uses and ethnopharmacological properties of T. kaiserana. Methods A search for available information on the medicinal uses and ethnopharmacological properties of T. kaiserana was conducted by searching the scientific databases such as SpringerLink®, PubMed®, Scopus®, Web of Science, Google Scholar, ScienceDirect®, and SciELO, as well as pre-electronic literature sources such as books, book chapters, and other publications obtained from the university library. Results Results from this research showed that the T. kaiserana is used as a diuretic and traditional medicine against HIV/AIDs opportunistic infections, skin diseases, backache, cardiac problems, headache, diuretic, vomiting, cough, bilharzia, diarrhoea, and gonorrhoea. The phytochemical assessment of T. kaiserana revealed that it contains castalagin, ellagic acid glycosides, ellagic acid rhamnoside, ellagitannin, gallic acid, gallotannins, punicalagin, punicalin, tannins, terchebulin, and terflavin-A. The crude extracts of T. kaiserana and phytochemical compounds isolated from the species exhibited antibacterial, antimycobacterial, antifungal, and antiproliferative activities. Conclusion Results of this study contribute to the existing traditional ecological knowledge about ethnomedicinal applications and ethnopharmacological properties of T. kaiserana that could be useful in bio-prospecting for new health-promoting and pharmaceutical products. Recommendations Future research on T. kaiserana should focus on detailed phytochemical, pharmacological, and toxicological evaluations, as well as in vivo and clinical studies.